PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN MOTIVASI KERJA TERHADAP KEPUASAN KERJA KARYAWAN (Studi Kasus Pada PT. Riau Pos Intermedia Pekanbaru) - Simanjuntak, Niko Hendarto; ", Kasmirudin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research aims to understand The Influence of Transformational Leadership Style and Work Motivation to The Employee Job Satisfaction (study at PT.Riau Pos Intermedia Pekanbaru). Transformational leadership style as X1 variable, work motivation as X2 variable, and job statisfaction as a Y variable.The methods of this research are descriptive and quantitative by using SPSS 20. The samples that had been used as many as 29 employees. The samples were determined by considering proportional sampling way which involved simple random sampling. Data collection technique by distributing questionnaires.The result of the analysis by using multiple linear regression, T test, and F test. It’s known that transformational leadership style has significant effect to the employee job statisfaction, work motivation has significant effect to the employee job statisfaction, and Transformational Leadership style and work motivation have significant effect to the Employee Job Statisfaction.Key words : Transformational Leadership Style, work environment, job statisfaction.